Analisis pola transportasi sedimen terhadap sebaran plankton dan daerah penangkapan ikan muara Sungai Kampar - Heru Purnomo; Rifardi Rifardi; Mubarak Mubarak (Jurnal Zona, 2018)
This study aimed to analyze the pattern of sediment transport to the distribution of plankton and fishing ground in the estuary of KamparRiver. This study used survey methods, the study sample was obtained in the field are considered to represent the Kampar River estuary. Then the sampling results in the form of TSS, brightness, temperature, salinity, pH, flow velocity and plankton descriptively analyzed and discussed with reference to data interpretation method by using mathematical models (software mike21 ). The results showed the concentration distribution of sediment at the mouth of the Kampar River in east monsoon amounted to 8.76 million tons / day and in the west monsoon amounted to 7.64 million tons / day. A region prone to silting due to sediment transport is periodically southeastern portion Mendol. Based on the analysis modeling , plankton diversity index tends to be low in the study site so that the waters around the Mendol island excluding strategic area for fishing grounds it is indicated there has been a downward trend in plankton diversity index as the primary productivity . The existence of TSS may hinder the penetration of light that ultimately affect the photosynthetic plankton.